Port Equipment Downtime Prediction and Lifetime Data Analysis: Evidence from a Case Study - Lot Okanminiwei; Sunday Ayoola Oke (JIEMS (Journal of Industrial Engineering and Management Systems), 2021)
Prediction of downtime and lifetime data for gantry cranes in a container terminal is a crucial concern for port terminals due to the requirement for maintenance planning and capital expenditure. Correct estimation of lifetime behavior for gantry cranes is complex since multiple cranes are involved, each with different costs, capacities; installation, and retirement dates. This paper develops statistically-oriented predictions for the lifetimes of container terminals company fleet of gantry cranes. Data records on downtime for cranes were collected and analyzed using Weibull, normal, and Rayleigh distributions regarding a port in southwestern Nigeria. The downtime, probability density function, cumulative density function, reliability, and hazard rate were analyzed for three shape functions of Weibull, β=0.5, 1, and 3. The same was analyzed for Rayleigh and normal distribution functions. The mean downtime was 30.58 hrs. The highest PDF, CDF, R(t) for all β =0.5, 1, and 3, were 0.26, 0.78, .030 and 13.13, respectively. However, the least values for these parameters are 0.01, 0.71, 0.25, and 0.04, respectively. These values are means for thirty data points and concern the Weibull distribution function. For the Rayleigh distribution, the mean PDF, CDF, R(t) and h(t) are 0.002, 0.042, 0.958 and 0.002 while they are 0.002, 0.456, 0.542 and 35.755 for the normal distribution. This article provides new insights into the lifetime analysis of gantry cranes in a container terminal.